LAYANAN BIMBINGAN KELOMPOK UNTUK MENGEMBANGKAN BERPIKIR POSITIF PADA KELAS VII SMP NEGERI 5 PONTIANAK - Susilawati, Asri; Asrori, Muhammad; Purwanti, Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractPositive thinking is very important because whatever we think will become our actions and whatever our actions, it will become our habits and behavior. If we want to behave well then we must think of things from a good persperctive too. It all comes from the mind, if we want to be successful then we must think that we must be successful because this gives rise to our actions, habits and behavior to be successful. The method in this research is descriptive method. Based on the results of data analysis group guidance services to develop positive thinking in class is 61% with medium category and after given services is 95% with high category. From the t-test there are significant differences in positive thinking before and after group guidance services are provided. Suggestions : (1) BK teachers are expected to be able to use positive languange, and accept all their heart. (2) for students are expected to be able to use positive language, dare to express opinions, believe in the answers they have, and be able to accept their own strengths. (3) the researcher is expected to be able to use positive language, and more confident his research can be successful.Â Keywords : Group Guidance, Positive Thinking